VB-DVFS: A new algorithm for power efficiency of CMP with GALS - Duan Wei; Fan Qi Fei; Huang Kun; Zhang Ge (2010 17th IEEE International Conference on Electronics, Circuits and Systems, 2010)
The advent of era of multi-core makes power consumption being the prime constraint of microprocessor design. The globally asynchronous locally synchronous (GALS) design of distributed clock network can excellently improve the power efficiency of single-chip multiprocessor (CMP) using dynamic voltage and frequency scaling (DVFS) policy. This paper proposes a new DVFS algorithm, which is used on CMP with GALS technology. The new algorithm, named Voting Based DVFS (VB-DVFS), dynamically adjusts voltage and frequency of processors in CMP according to the information of architecture and program behaviors. According to the experimental results, our algorithm reduces 24.8% power consumption, while just causing 9.9% performance loss.